2015
DOI: 10.1007/s12639-015-0686-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal incidence of parasitic diseases in bovines of south western Gujarat (Junagadh), India

Abstract: The current study was conducted to investigate the incidence of parasitic diseases in bovines which were sick and brought at veterinary hospital for treatment. A total of 366 samples were investigated from cattle (n = 175) and buffaloes (n = 191) presented at Teaching Veterinary Clinical Complex (TVCC), Veterinary College, Junagadh, Gujarat during January to December 2014. Examination of Giemsa-stained peripheral blood smears exhibited that 58.6 % of cattle and 41.2 % of buffaloes were infected with haemoparas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 12 publications
5
22
1
1
Order By: Relevance
“…The highest prevalence of helminths parasitic infections (65.0%) was recorded in November which was included in the rainy season and lowest prevalence (37.5%) was recorded in January which was categorized in dry season. This finding was in agreement with Wadhwa et al 36 and Kumar et al 37 who recorded higher incidence of parasitic infection during rainy season and lower prevalence during dry season. This may be due to high-moisture content and temperature which favours the growth and development of larvae on pasture resulting in increased contact between the host and parasites.…”
Section: Discussionsupporting
confidence: 93%
“…The highest prevalence of helminths parasitic infections (65.0%) was recorded in November which was included in the rainy season and lowest prevalence (37.5%) was recorded in January which was categorized in dry season. This finding was in agreement with Wadhwa et al 36 and Kumar et al 37 who recorded higher incidence of parasitic infection during rainy season and lower prevalence during dry season. This may be due to high-moisture content and temperature which favours the growth and development of larvae on pasture resulting in increased contact between the host and parasites.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations correlate with the results of previous studies Vohra et al, 2012). In contrast, Kumar et al (2016), reported significantly higher prevalence of haemoparasites in bovines in south-western Gujarat. This may be due to collection of samples specifically from clinically suspected animals.…”
Section: Relative Efficacy Of Conventional Parasitological Technique supporting
confidence: 92%
“…In this work, summer and autumn are the most seasons where Eimeria infection is more likely to occur. It might be because summer where the climate there is very hot and that might be a stressful factor to the animals that leads to more shedding of the protozoa while autumn shows an increased level of infection due to the humidity which is more favorable for sporulation of oocysts [25] . Infection with Eimeria is considered to be a risk factor when the infected animals are exposed to any stress condition such as transportation or underfeeding and the associated ailments are likely to perturb the immune system, where Eimeria species could propagate intensively in the intestine and result in outbreak [1] .…”
Section: Discussionmentioning
confidence: 99%